Effects of pH on uranium uptake and oxidative stress responses induced in Arabidopsis thaliana. (26th July 2013) - Saenen, Eline; Horemans, Nele; Vanhoudt, Nathalie; Vandenhove, Hildegarde; Biermans, Geert; Van Hees, May; Wannijn, Jean; Vangronsveld, Jaco; Cuypers, Ann
Abstract: Uranium (U) causes oxidative stress in Arabidopsis thaliana plants grown at pH 5.5. However, U speciation and its toxicity strongly depend on environmental parameters, for example pH. It is unknown how different U species determine U uptake and translocation within plants and how they might affect the oxidative defense mechanisms of these plants. The present study analyzed U uptake and oxidative stress‐related responses in A. thaliana (Columbia ecotype) under contrasted U chemical speciation conditions. The 18‐d‐old seedlings were exposed for 3 d to 25 µM U in a nutrient solution of which the pH was adjusted to 4.5, 5.5, 6.5, or 7.5. Results indicate that there is a different rate of U uptake and translocation at the different pHs, with high uptake and low translocation at low pH and lower uptake but higher translocation at high pH. After U exposure, an increased glutathione reductase activity and total glutathione concentration were observed in U‐exposed roots, pointing toward an important role for glutathione in the root defense system against U either by chelation or by antioxidative defense mechanisms. In leaves, antioxidative defense mechanisms were activated on U exposure, indicated by increased superoxide dismutase and catalase activity. As it seems that U toxicity is influenced by pH, it is important to consider site‐specific characteristics when making U risk assessments. Environ Toxicol Chem 2013;32:2125–2133. © 2013 SETAC